Application of Hosaka and DJ Kim Whatmann paper protocols for rapid isolation of cowpea DNA - Yusuf, M.; Muranaka, S.; Zaria, A.A. (2009)
The traditional liquid nitrogen DNA extraction method is expensive and tedious. There is, therefore, the need for cheaper and faster methods of DNA extraction for efficient application of marker assisted selection (MAS) for breeding for striga resistance in cowpea to be able to handle large number of samples at a time. Two DNA extraction methods; Hosaka (2004) and DJ Kim Whatmann paper (unpublished) were tested on cowpea line IT06K-5-83 under different conditions. The results revealed that both methods with modifications can work with cowpea. However, Hosaka (2004) method seems to be more promising than the other method for DNA extraction in cowpea because it gives better and more consistent DNA band.